Measuring size distributions of atmospheric aerosols using natural air ions. Issue 7 (3rd July 2022) - Li, Yiran; Chen, Xiaotong; Jiang, Jingkun
Abstract: Electrical mobility size spectrometers are widely used to measure ambient aerosol number size distributions. A key component of these mobility systems is the charge conditioner, or neutralizer, which is used to place a stationary charge distribution on the aerosols prior to mobility analysis. Yet, there are natural air ions in the atmosphere which are constantly conditioning the charge state of atmospheric aerosols. In this study, we demonstrate that this natural charging process can be utilized by these spectrometers to measure size distributions of atmospheric aerosols without using a conventional neutralizer. This is achieved by measuring charged particles of both polarities, in contrast to only one polarity as conventionally done. The bipolar data is used to retrieve air ion properties from which the aerosol charge fractions are calculated. We deployed this new method in urban Beijing to measure atmospheric aerosols over a period of two years and verified that size distributions can be effectively measured using natural air ions. There is good agreement in aerosol size distributions when comparing this new method to a conventional spectrometer, and good agreement in total particle number concentrations measured by a condensation particle counter. Additionally, measuring charged particles of both polarities makes the uncertainties due to aerosol charging now traceable. We show that during two years of measurement in urban Beijing, the properties of ions produced by conventional neutralizers drifted due to the aging of ion sources, while the properties of natural atmospheric ions remained stable over time, despite occasional short-period fluctuations. Graphical Abstract: UF0001 Copyright © 2022 American Association for Aerosol Research